Continuous microwave-assisted in-situ transesterification of lipids in seeds of invasive Chinese tallow trees (Triadica sebifera L.): Kinetic and thermodynamic studies. (December 2017) - Barekati-Goudarzi, Mohamad; Muley, Pranjali D.; Clarens, Andres; Nde, Divine B.; Boldor, Dorin
Abstract: Continuous in-situ transesterification of Chinese tallow tree seeds into methyl esters using a resonant focusing cavity microwave coupled with a CSTR system was investigated. High production yield of 90% with 97% conversion rate was obtained in 24 min CSTR residence time at a methanol/hexane/Chinese tallow tree seed mass ratio of 47.5:39.3:20, a continuous microwave heating power of 290 W and 14 s exposure time, reaction temperature of 60 °C in presence of sodium hydroxide catalyst (4 g NaOH per 100 g oil). The experimental data fits first order reaction kinetics. The values of rate constants at different temperatures and the corresponding activation energy were found out to be 0.08–0.084 min −1 and 2057.4 J mol −1, respectively. Thermodynamic parameters values such as Gibbs free energy ( ΔG ), enthalpy ( ΔH ) and entropy of activation ( ΔS ) were also determined. The positive values of ΔG and small negative value of ΔH indicated that the reaction has an unspontaneous/endergonic nature and is slightly exothermic. Graphical abstract: Highlights: Microwave-assisted in-situ transesterification process of CTT seeds was time and energy efficient. 90% production yield with 97% reaction conversion rate of CTT seeds into FAME were achieved. The first order kinetic model fits well to the overall transesterification reaction with above 90% prediction accuracy. In-situ transesterification reaction of CTT seeds was non-spontaneous, slightly exothermic with negative entropy change.